Economics of Small Scale Deep Litter System of Egg Production in Oredo Local Government Area of Edo State, Nigeria - Ekunwe, P.A.; Soniregun, O.O.; Oyedeji, J.O. (International Journal of Poultry Science, 2005)
The general objective of this study is to examine the economics of small-scale deep litter system of egg production in Oredo Local Government Area Edo State, Nigeria. The Specific objectives are to determine the profitability in deep litter system of poultry production among small-scale farmers, to examine the socioeconomic characteristics of egg producers and to identify the constraints to egg production in the study area. Primary and secondary data were obtained from farmers. A purposive sampling of small-scale egg producers was carried first in the study area. Then a simple random sampling technique was then employed to select 182 egg producers using a well-structured questionnaire from the entire population of small-scale farmers. Descriptive statistics such as means and percentages were using to examine the socioeconomic characteristics. The gross margin analysis was used to determine the profitability. While the constraints to egg production was analyzed using the likert scale technique. The result of the analysis reveals that the average number of birds raised in deep litter is 760 birds. The study also shows that 68% and 32% of women and men produce eggs at this level respectively. The result of the study reveals that the fixed capital investment per bird was N 624.17 and total fixed cost less depreciation per bird was N.208.88 and total variable cost per bird was N 331.62. The study also reveals that total revenue from the sales of eggs per and other sources were N 3,749.22 per bird with a gross margin per bird of N 3,417.6 and a net profit of N 3,208.72. Finally the major constraints faced by the farmers are in the order of inadequate finance, high cost of feed, low egg price and high cost of medicine and vaccine Investments on Poultry building.